Mapping of Tsunami disaster evacuation pathways based on Tsunami altitude scenario using Network Analyst Method (case study: Palu City, Central Sulawesi) - I Made Edy Kusuma Putra; Hanna Prillysca Chernovita (Journal of Applied Geospatial Information, 2020)
Central Sulawesi's Palu city is one of the regions in Indonesia that is vulnerable to tsunami disasters. A tsunami disaster is a disaster that can cause many victims of both casualties and materials. One of the disaster mitigation to reduce the victim's fall is by evacuating the community to a safer place, to evacuate the population required evacuation routes that can direct people to evacuation sites. The purpose of this research is to make a tsunami runoff using cost distance and to make tsunami evacuation and use a Network analyst on Arcgis 10.4 software. The most affected regional analysis is the Northern Palu sub-district with a total area of 8.643528 km2, and there are 93 evacuation routes with 92 evacuation points. The longest evacuation route is 4,297 M with a travel time of 27.6 minutes with running and the shortest evacuation route of 96 m with a travel time of 0.6 minutes by running.